1999
DOI: 10.1007/pl00011809
|View full text |Cite
|
Sign up to set email alerts
|

Predator Avoidance of Transgenic Channel Catfish Containing Salmonid Growth Hormone Genes

Abstract: Transgenic channel catfish (Ictalurus punctatus) containing salmonid growth hormone genes can grow 33% faster than normal channel catfish under aquaculture conditions. However, before transgenic catfish are released and utilized by the private sector, their genetic impact on the natural environment must be examined. Predator avoidance is one of the major fitness traits determining potential environmental risk. To determine the predator avoidance ability and growth performance of transgenic catfish in a natural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
20
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(24 citation statements)
references
References 13 publications
3
20
0
1
Order By: Relevance
“…They suggested that any ecological effect would be unlikely because the increased susceptibility of transgenic channel catfish to predators would most likely decrease or eliminate the transgenic genotype if they were to be released into nature [24]. Similar results were also found in a study by Abrahams and Sutterlin [25].…”
Section: Viability Of Transgenic Fishsupporting
confidence: 63%
See 1 more Smart Citation
“…They suggested that any ecological effect would be unlikely because the increased susceptibility of transgenic channel catfish to predators would most likely decrease or eliminate the transgenic genotype if they were to be released into nature [24]. Similar results were also found in a study by Abrahams and Sutterlin [25].…”
Section: Viability Of Transgenic Fishsupporting
confidence: 63%
“…Dunham et al studied the predator avoidance of GH transgenic channel catfish (Ictalurus punctatus) and found that overall predator avoidance was also better for non-transgenic individuals [24]. They suggested that any ecological effect would be unlikely because the increased susceptibility of transgenic channel catfish to predators would most likely decrease or eliminate the transgenic genotype if they were to be released into nature [24].…”
Section: Viability Of Transgenic Fishmentioning
confidence: 99%
“…(Martinez et al, 1999;Rahman et al, 1998) and common carp (Cyprinus carpio L.) (Wang et al, 2001;Zhong et al, 2012). During recent years, it has become clear that elevated growth hormone (GH) levels in transgenic fish induce a wide range of effects apart from growth promotion (Devlin et al, 1994;Du et al, 1992;Martinez et al, 1996;Nam et al, 2001;Rahman et al, 1998;Wang et al, 2001;Zhong et al, 2012), including altered metabolism (Guan et al, 2008;McKenzie et al, 2003;Stevens et al, 1998), swimming performance (Farrell et al, 1997;Lee et al, 2003;Stevens et al, 1998), anti-predator behavior (Abrahams and Sutterlin, 1999;Duan et al, 2010;Dunham et al, 1999) and growth-related neuroendocrine regulation (Raven et al, 2008). In addition, GH treatment resulted in increased food intake and feeding behavior in normal fish (Johnsson and Bjornsson, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…This concern has led to numerous articles on the conceptual problem of ecological risk-assessment (8)(9)(10), and several laboratory and theoretical studies have addressed the fitness and/or ecological consequences of transgenic animals (11)(12)(13)(14)(15)(16)(17). However, except for a few field trials on nematodes and mites, few empirical studies to evaluate the direct ecological effects of transgenic animals in more natural environments have been undertaken (18,19).…”
mentioning
confidence: 99%